2017
DOI: 10.4238/gmr16029592
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Beta Casein Gene and analysis of milk characteristicsin Gir and Guzerá dairy cattle

Abstract: ABSTRACT. Several human health problems have been related to the allergenic constitution of bovine milk due to the body's immune reaction to milk proteins. It is necessary find solutions to minimize the occurrence of such reactions, given the importance of milk as a source of animal protein. The aim of this study was to evaluate the allelic frequency of the CSN2 gene and to evaluate differences in the characteristics of Gir and Guzerá bovine milk. One hundred and fifty-six cows were used (68 Gir and 88 Guzerá)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 9 publications
1
19
1
3
Order By: Relevance
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The significant association reported for lactose percentages in Egyptian Baladi cows indicates that the ABCG2-HhaI-AA genotype is associated with higher lactose and lower milk yields than the AB genotype. This difference may be due to the negative correlation between milk yield (kg) and lactose (Rangel et al, 2017). Thus, the ABCG2-HhaI-AA genotype could be incorporated into marker-assisted selection for culling of this genotype due to its association with lower milk yields.…”
Section: Discussionmentioning
confidence: 99%
“…Nos estudos já realizados sobre as variantes A1 e A2 da β-caseína, foram descritas as variações nas frequências gênicas (alélicas) tanto de raçascomumente utilizadas para a produção leiteira, quanto de raças locais.A frequência do alelo A2 é menor nas raças taurinas, à exceção da raça Guernsey (variando de 0,88 a 0,97), provavelmente pelo seu rebanho mais fechado e com menor número de animais. A maior frequência (%) deste alelo é descrita nas raças zebuínas, como segue: Angus (0,05), Ayrshire (0,28-0,52), Brahan (0,01), Gir (0,88-0,98), Guzerá (0,97), Hereford (0,20), Holandesa (0,25-0,55), Jersey (0,49-0,72), Pardo Suíça (0,49-0,72), Shorthorn (0,51), Simental (0,56-0,63) e Vacas Vermelhas Nórdicas (0,23) [12,4,8,13,14,15] .…”
Section: Rebanhos Geneticamente Selecionadosunclassified